Algeria's Role in the War of Attrition between the Political Context and Mmilitary Act (the Egyptian fron1967-1970) - BENMAZOUZ, Ameur (Journal of Human Sciences, 2020)
The present study highlights the great role played by Algeria over the years of the War of Attrition (1967-1970) to support the Egyptian front facing the Israeli aggression. It used all its diplomatic apparatus as well as its economic and military capabilities to serve the Arab and Egyptian cause in particular, at the expense of the internal challenges facing it at that time and transcending all considerations of its regional security and geographical distance from the confrontational countries. This showed presenting interest in the Arab nation over its own interests, in compliance with its national principles. Algeria supported the war on the Egyptian front within the framework of a comprehensive plan that takes into account the stolen rights of the Palestinians. The Algerian army squads participated actively in attrition fights on the Egyptian front, and were able to thwart most of the Israeli retaliatory attacks supporting the Egyptian forces in many raid operations against the Israeli enemy, and thus the war of attrition contributed - albeit relatively - to mitigating the effects of the 1967 defeat. On the other hand, it was a practical preparation for the victory of the October 1973 war.